Isolation, homology modeling and renal effects of a C-type natriuretic peptide from the venom of the Brazilian yellow scorpion (Tityus serrulatus) - Alves, Renata S.; Ximenes, Rafael M.; Jorge, Antonio R.C.; Nascimento, Nilberto R.F.; Martins, René D.; Rabello, Marcelo M.; Hernandes, Marcelo Z.; Toyama, Daniela O.; Toyama, Marcos H. [UNESP]; Martins, Alice M.C.; Havt, Alexandre; Monteiro, Helena S.A. (Elsevier, 2013)
Mammalian natriuretic peptides (NPs) have been extensively investigated for use as therapeutic agents in the treatment of cardiovascular diseases. Here, we describe the isolation, sequencing and tridimensional homology modeling of the first C-type natriuretic peptide isolated from scorpion venom. In addition, its effects on the renal function of rats and on the mRNA expression of natriuretic peptide receptors in the kidneys are delineated. Fractionation of Tityusserrulatus venom using chromatographic techniques yielded a peptide with a molecular mass of 2190.64Da, which exhibited the pattern of disulfide bridges that is characteristic of a C-type NP (TsNP, T. serrulatus Natriuretic Peptide). In the isolated perfused rat kidney assay, treatment with two concentrations of TsNP (0.03 and 0.1μg/mL) increased the perfusion pressure, glomerular filtration rate and urinary flow. After 60min of treatment at both concentrations, the percentages of sodium, potassium and chloride transport were decreased, and the urinary cGMP concentration was elevated. Natriuretic peptide receptor-A (NPR-A) mRNA expression was down regulated in the kidneys treated with both concentrations of TsNP, whereas NPR-B, NPR-C and CG-C mRNAs were up regulated at the 0.1μg/mL concentration. In conclusion, this work describes the isolation and modeling of the first natriuretic peptide isolated from scorpion venom. In addition, examinations of the renal actions of TsNP indicate that its effects may be related to the activation of NPR-B, NPR-C and GC-C. © 2013 Elsevier Ltd.
Keywords: Guanylate cyclase C; Kidney perfusion; Natriuretic peptide; Natriuretic peptide receptor; Tityus serrulatus; chloride; cyclic GMP; endothelial nitric oxide synthase; messenger RNA; mitogen activated protein kinase 1; natriuretic peptide receptor A; natriuretic peptide receptor B; natriuretic peptide receptor C; natriuretic peptide type C; potassium; scorpion venom; sodium; chloride transport; controlled study; eNOS gene; gene; gene expression; glomerulus filtration rate; male; MAPK 1 gene; micturition; molecular weight; nonhuman; nucleotide sequence; potassium transport; priority journal; protein isolation; rat; scorpion; sequence alignment; sequence analysis; sodium transport; tityus serrulatus; toxin analysis